A short course in international business ethics : combining ethics and profits in global business - Mitchell, Charles, 1953- (Short course in international trade series., 2009)
A Short Course in International Business Ethics identifies the key ethical issues facing international businesspeople and gives the reader practical tools to use in everyday situations.